The Impact of Positive Margins on Outcome Among Patients With Gastric Cancer Treated With Radiation. (June 2016) - Schoenfeld, Jonathan D.; Wo, Jennifer Y.; Mamon, Harvey J.; Kwak, Eunice L.; Mullen, John T.; Enzinger, Peter Z.; Blaskowsky, Lawrence S.; Ryan, David P.; Hong, Theodore S.
Abstract : Objectives: Positive surgical margins have been associated with worse outcomes in gastric cancer patients. We evaluated the impact of positive margins in a modern cohort treated with radiotherapy. Methods: We performed a multi-institutional retrospective analysis of patients treated from 1998 through 2010. All underwent definitive surgery and were followed up for recurrence and survival. We assessed associations with positive margins using the log-rank tests and Cox proportional hazard models. Results: We identified 91 patients with a median follow-up of 42 months. Seven received radiation before surgery; the remainder were treated postoperatively. Epirubicin-based chemotherapy was given to 8 patients perioperatively and 25 postoperatively. Nineteen had positive margins (21%), including 25% of patients who received chemotherapy perioperatively. All patients who received neoadjuvant radiotherapy had negative margins. There were 41 recurrences and 44 deaths. Positive margins were associated with increased recurrence risk after adjusting for other factors (hazard ratio=2.8, P =0.01). In addition, median survival with positive margins was 31 months as compared with 77 months after complete resection ( P =0.13). Conclusions: Positive margins were associated with recurrence despite aggressive multimodality therapy including radiotherapy and the selective use of chemotherapy. Thus, additional consideration is warranted for strategies such as neoadjuvant chemoradiation intended to facilitate complete resection.